Calpain inhibitor MDL28170 improves the transplantation-mediated therapeutic effect of bone marrow-derived mesenchymal stem cells following traumatic brain injury - Jiangnan Hu; Lefu Chen; Xujun Huang; Ke Wu; Saidan Ding; Weikan Wang; Brian Wang; Charity Smith; Changhong Ren; Haoqi Ni; Qichuan ZhuGe; Jianjing Yang (Stem Cell Research & Therapy, 2019)
Abstract Background Studies have shown that transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) protects against brain damage. However, the low survival number of transplanted BMSCs remains a pertinent challenge and can be attributed to the unfavorable microenvironment of the injured brain. It is well known that calpain activation plays a critical role in traumatic brain injury (TBI)-mediated inflammation and cell death; previous studies showed that inhibiting calpain activation is neuroprotective after TBI. Thus, we investigated whether preconditioning with the calpain inhibitor, MDL28170, could enhance the survival of BMSCs transplanted at 24 h post TBI to improve neurological function. Methods TBI rat model was induced by the weight-drop method, using the gravitational forces of a free falling weight to produce a focal brain injury. MDL28170 was injected intracranially at the lesion site at 30 min post TBI, and the secretion levels of neuroinflammatory factors were assessed 24 h later. BMSCs labeled with green fluorescent protein (GFP) were locally administrated into the lesion site of TBI rat brains at 24 h post TBI. Immunofluorescence and histopathology were performed to evaluate the BMSC survival and the TBI lesion volume. Modified neurological severity scores were chosen to evaluate the functional recovery. The potential mechanisms by which MDL28170 is involved in the regulation of inflammation signaling pathway and cell apoptosis were determined by western blot and immunofluorescence staining. Results Overall, we found that a single dose of MDL28170 at acute phase of TBI improved the microenvironment by inhibiting the inflammation, facilitated the survival of grafted GFP-BMSCs, and reduced the grafted cell apoptosis, leading to the reduction of lesion cavity. Furthermore, a significant neurological function improvement was observed when BMSCs were transplanted into a MDL28170-preconditioned TBI brains compared with the one without MDL28170-precondition group. Conclusions Taken together, our data suggest that MDL28170 improves BMSC transplantation microenvironment and enhances the neurological function restoration after TBI via increased survival rate of BMSCs. We suggest that the calpain inhibitor, MDL28170, could be pursued as a new combination therapeutic strategy to advance the effects of transplanted BMSCs in cell-based regenerative medicine.